2003
DOI: 10.1191/1352458503ms958oa
|View full text |Cite
|
Sign up to set email alerts
|

Disability in multiple sclerosis is related to normal appearing brain tissue MTR histogram abnormalities

Abstract: There is evidence of diffuse abnormalities in NABT in addition to global brain atrophy in relapse onset MS patients, including those with recently diagnosed RRMS and benign MS. The abnormalities are greatest in patients with the more disabling SPMS. Atrophy, NABT and lesion abnormalities are all partly correlated; the processes marked by these MR measures all contribute to disability in MS, providing complementary information relevant to the complex pathological processes that occur in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…To have a comprehensive picture of the patients studied, we also investigated the possible structural correlates of fMRI abnormalities in these patients, by assessing global brain damage, in terms of T 2 -visible lesions, brain volume, NAWM and GM involvement, and regional damage of WM fiber bundles variously related with the cognitive tasks investigated. In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To have a comprehensive picture of the patients studied, we also investigated the possible structural correlates of fMRI abnormalities in these patients, by assessing global brain damage, in terms of T 2 -visible lesions, brain volume, NAWM and GM involvement, and regional damage of WM fiber bundles variously related with the cognitive tasks investigated. In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, magnetic resonance imaging (MRI) has provided combersome and controversial results. In detail, the majority of the studies showed that the load of T 2 -visible lesions is similar between patients with BMS and those with other disease phenotypes, whereas the extent of normal-appearing brain tissue (NABT) damage was found to be less pronounced in patients with BMS than in other forms of the disease in some studies [Davie et al, 1999;De Stefano et al, 2006;Falini et al, 1998;Filippi et al, 1996Filippi et al, , 1999Filippi et al, , 2000, but not in others [Brass et al, 2004;Droogan et al, 1999;Horsfield et al, 1996;Traboulsee et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such measures are sensitive in depicting subtle abnormalities in NAWM and NAGM and convincing evidence has emerged that increasing abnormality in these tissues is associated with clinical progression. 99,100 However, these subtle MR changes are pathologically nonspecific and could potentially represent the effects of inflammation, gliosis, or axonal loss, all of which occur in NAWM. 4,101 Although they may be valuable for monitoring clinically relevant disease progression they should not be considered as specific markers of neurodegeneration.…”
Section: Other Measuresmentioning
confidence: 99%
“…The application of non-conventional magnetic resonance imaging (MRI) techniques, such as magnetization transfer imaging, magnetic resonance spectroscopy, and diffusion tensor imaging, has led to only modest achievements in linking imaging data with clinical measures of disease severity for neurologic disorders in general and for multiple sclerosis (MS) in particular. Alternately, OCT has been incorporated with increasing frequency as an exploratory outcome in treatment trials, observational studies, and even clinical practice in order to achieve a greater understanding of the relationship between changes in retinal structure and patient reported outcomes of visual function [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%